[Edgley, Eric and Dawe, Clem (comedians/directors/theatrical entrepreneurs) : programs and related material collected by the National Library of Australia]
Material in the Australian performing arts programs and ephemera (PROMPT) collection consists of programs and related items for Australian performing arts organisations, Australian artists performing overseas, professional productions performed in Australia (including those featuring overseas performers) and overseas performances of Australian plays, music, etc.
English vaudeville brothers Eric Edgley (1899-1967) and Clem Dawe (d.1955) were invited to Australia in 1920 by J&N Tait to appear in a production of Sinbad the Sailor at King's Theatre, Melbourne. They were originally born Eric and Clem White, and changed their names in their early years to stage names. The partnership later toured Australia for theatre manager J. C. Williamson, and played in shows including Robinson Crusoe, Love Lies and So This Is Love, and then toured Australasia, the United Kingdom and South Africa, doing shows under various arrangements, and moving from performers to promoters. In 1951 they moved to Perth, Western Australia to manage His Majesty's Theatre, taking a lease on the venue in 1954. Clem Dawe died the following year. In 1958 the company purchased His Majesty's Theatre and undertook extensive renovation work. From the early 1960s Eric Edgley arranged tours to Australasia from Russian performing troupes including the Bolshoi Ballet, the Georgian State Dance Company and the Moscow Variety Theatre. Edgley also promoted local talent including the West Australian Ballet. Eric died in 1967 and management of the company was taken over his then 23-year-old son Michael Edgley. See separate PROMPT file and for Edgley International Pty Ltd: http://nla.gov.au/nla.cat-vn6533667
This collection is featured in the Guide to Australian Performing Arts Programs and Ephemera (PROMPT) Collections in the National Library of Australia
Keywords: Edgley, Eric -- Miscellanea; Dawe, Clem -- Miscellanea; Actors -- Australia -- Miscellanea; Entertainers -- Australia -- Miscellanea; Theatrical producers and directors -- Miscellanea; Theatrical agents -- Australia -- Miscellanea; Theater programs -- Australia; Performing arts -- Australia; Printed ephemera -- Australia; Australian